On the density of states of graphene in the nearest-neighbor approximation - Ananyev, V.O.; Ovchynnikov, M.I. (Condensed Matter Physics, 2017)
We propose an alternative analytical expression for the density of states of a clean graphene in the nearestneighbor approximation. In contrast to the previously known expression, it can be written as a single formula
valid for the whole energy range. The correspondence with the previously known expression is shown and the
limiting cases are analyzed. Ми пропонуємо альтернативний аналiтичний вираз для густини електронних станiв у чистому графенi в наближеннi найближчих сусiдiв. На противагу вже вiдомим виразам, вiн представляє собою єдину
формулу, справедливу на всьому iнтервалi енергiй. Також було перевiрено вiдповiднiсть уже вiдомим
виразам i дослiджено граничнi випадки.